The Rendering of Foul Language in Spanish-English Subtitling: The Case of El Vecino - Barrera-Rioja, Noemí (Íkala, Revista de Lenguaje y Cultura, 2023)
Audiovisual translation into English is recently gaining importance as the material produced in other languages is now increasingly crossing borders thanks to the internet. This article explores foul language, deemed one of the most problematic aspects of subtitling. The aim is to elucidate how this is normally subtitled into English. Drawing on a corpus of swearwords from Netflix Spanish comedy series El Vecino (Vigalondo, 2019‒2021), this paper examines the frequency of use of different translation techniques and the reasons behind the omission of certain instances of foul language. Results show that, while omitting swearwords is the second most common scenario, the most frequent one is transferring the offensive load of the original expression, with roughly 70 % of instances making it into the target product. As for factors influencing this decision, it was observed that overall swearwords are omitted not because they are offensive, but primarily because of their low narrative value, the subtitling’s vulnerability, and the interaction between swearwords and non-verbal elements. Time and space constraints of subtitling appear to have little impact. These results suggest that the potential influence of censorship and cultural differences on foul language omissions in English subtitles is presented as a possible research avenue.